2007
DOI: 10.1107/s1600536807050519
|View full text |Cite
|
Sign up to set email alerts
|

2-(Pyrrolidin-1-ylmethyl)isoindoline-1,3-dione

Abstract: Key indicators: single-crystal X-ray study; T = 293 K; mean (C-C) = 0.003 Å; R factor = 0.044; wR factor = 0.133; data-to-parameter ratio = 17.8. organic compounds o4388 # 2007 International Union of Crystallography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The 1 H NMR spectrum of synthesized Mannich base showed four signals indicating four different types of protons. The crystal structure of synthesized Mannich base was already reported [24] and hence mass spectral study was not attempted. Thus based on physical, chemical and crystallographic studies the molecular structure is confirmed as given in Fig.…”
Section: Structural Characterization Of Mannich Basementioning
confidence: 99%
“…The 1 H NMR spectrum of synthesized Mannich base showed four signals indicating four different types of protons. The crystal structure of synthesized Mannich base was already reported [24] and hence mass spectral study was not attempted. Thus based on physical, chemical and crystallographic studies the molecular structure is confirmed as given in Fig.…”
Section: Structural Characterization Of Mannich Basementioning
confidence: 99%